Clinical Practice Observation of Trastuzumab in Patients with Human Epidermal Growth Receptor 2‐Positive Metastatic Adenocarcinoma of the Stomach or Gastroesophageal Junction. (4th June 2020) - Al‐Batran, Salah‐Eddin; Moorahrend, Enno; Maintz, Christoph; Goetze, Thorsten O.; Hempel, Dirk; Thuss‐Patience, Peter; Gaillard, Vincent E.; Hegewisch‐Becker, Susanna
Abstract: Background: The observational study HerMES collected primary data on effectiveness and safety of trastuzumab in patients with human epidermal growth receptor 2 (HER2)‐positive cancer of the stomach or gastroesophageal junction (GEJ) in routine clinical practice, exploring the treatment with trastuzumab, chemotherapy backbones used, and the HER2 testing in a real‐world setting in Germany. Subjects, Materials, and Methods: This noninterventional study observed patients with histologically confirmed, HER2‐positive metastatic adenocarcinoma of the stomach or GEJ, who were treated with trastuzumab according to the physicians' judgement and clinical practice. The observation phase per patient took as long as the duration of the trastuzumab therapy, but for a maximum of 12 months. A subsequent extended follow‐up phase lasted until the patient's death or the end of the study, that is, 2 years from start of the follow‐up phase of the last patient. All data were analyzed descriptively. Results: Between February 2010 and July 2016, 364 patients were observed at 171 sites throughout Germany. The median overall survival was 14.1 months and the median progression‐free survival was 7.9 months. The overall response rate was 43%. Safety was in line with previous reports. This study observed a high diversity of chemotherapy regimens that were combined with trastuzumab. Post hoc subgroup analyses showed differences in outcomes according to the chemotherapy regimen used. Conclusion: Trastuzumab treatment in everyday practice as observed in HerMES confirmed the positive results of the pivotal study ToGA in an observational, real‐world setting. Implications for Practice: Real‐world data of trastuzumab treatment of patients with gastroesophageal or gastric metastatic adenocarcinoma confirmed the positive results of the pivotal clinical trial. The observed median overall survival was 14.1 months and the median progression‐free survival was 7.9 months. Although recommendations concerning administration of trastuzumab were well implemented, a high diversity of chemotherapy regimens were combined with trastuzumab. Regimens other than the in‐label regimens, especially oxaliplatin‐based doublets or 5‐fluorouracil, leucovorin, oxaliplatin, taxane triplets, were used in 29% of patients. Observation of a second, marginal HER2‐positivity population confirmed the benefit of trastuzumab predominantly for well‐confirmed human epidermal growth receptor 2 (HER2)‐positive tumors and the requirement of reliable HER2 testing. Abstract : This article reports the results of the HerMES study on the use of trastuzumab for patients with gastric and gastro‐esophageal junction carcinoma in a real‐world setting in Germany.